Morphological changes of bacterial model membrane vesicles. Issue 9 (22nd July 2014) - Meister, Annette; Finger, Sebastian; Hause, Gerd; Blume, Alfred
<x xml:space="preserve">Abstract</x> Unilamellar vesicles frequently serve as model membrane systems to study membrane‐peptide and membrane‐protein interactions. They are formed either from natural lipid extracts that contain complex lipid mixtures, or from synthetic one‐, two‐, or multi‐component lipid mixtures mimicking the lipid composition of biological membranes. Unilamellar vesicles can be prepared by extrusion of aqueous multilamellar phospholipid suspensions and they can have limited stability due to aggregation and fusion processes. We used cryo‐transmission electron microscopy (cryoTEM) to study the morphology of vesicles of phosphatidylethanolamines (PEs), phosphatidylglycerols (PGs), and cardiolipins (CLs) that represent the major lipid components of cytoplasmic membranes of Gram‐negative bacteria. Our results show that single‐component vesicles of PE and PG stored at RT are stable in shape and size for at least 1 wk. In contrast, two‐component vesicles of PE/PG and PE/CL transform into lamellar sheets already several hours after preparation, which is probably due to a compensation of different spontaneous curvatures of PG lipids compared to PE and CL. With this investigation we intend to alert researchers working with model membranes to scrutinize the shape and stability of vesicles before using them in protein‐vesicle interaction studies. Practical applications: Liposomes represent widely‐used model membrane systems that are applied to mimic natural membranes. Usually, these liposomes are composed of one or two lipid components representing the major lipid constituents of the respective natural membrane. Their long‐term shape, aggregation, and fusion stability is an important prerequisite for the study of peptide‐liposome and protein‐liposome interactions, where the binding of peptides or proteins can have serious impacts on the liposomal shape and size. Furthermore, shape and size stability is of outstanding importance for the application of liposomes as drug‐delivery system. We showed that single‐component liposomes composed of the major lipid components of cytoplasmic membranes of Gram‐negative bacteria (PE and PG) are stable in shape and size for at least 1 wk, whereas the corresponding two‐component liposomes become unstable within hours and transform into discs and sheets. This knowledge will be indispensable for future studies on interactions of liposomes with peptides and proteins. <inline-graphic xlink:href="ark:/27927/pgh18r8vrw5" content-type="ejlt201300388-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Cryo‐transmission electron microscopy is the method of choice to study the size, morphology, and shape stability of liposomes being composed of the phospholipids PE, PG, and CL that represent the major lipid components of cytoplasmic membranes of Gram‐negative bacteria.